2012
DOI: 10.1159/000342201
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Agmination of Lymphomatoid Papulosis: An Ongoing Debate

Abstract: Background: Persistent agmination of lymphomatoid papulosis (PALP) has been a matter of controversy in the literature, some authors suggesting that it represents composite lymphoma, others localized lymphomatoid papulosis (LyP). Patient and Methods: A 64-year-old man was referred to our outpatient center complaining of papular eruptions lasting 3 years. At physical examination, he showed papulonodular lesions on the trunk and extremities. Some patches on the trunk and upper arms were also observed. Both types … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 20 publications
0
1
0
1
Order By: Relevance
“…No entanto, as lesões de linfoma cutâneo primário de grandes células B anaplásico geralmente são de maiores dimensões e, apesar de poderem resolver espontaneamente à semelhança da PL, não apresentam carácter recorrente. 1 A PL clássica pode associar-se a linfomas, sobretudo micose fungóide, linfoma cutâneo primário de grandes célu-las B anaplásico e doença de Hodgkin, 10 numa frequência que tem sido difícil de estabelecer, variando entre 10% a 20%, até 40% a 60% em estudos mais recentes. 10 Gruber et al estimou um risco cumulativo de 80% de desenvolver um linfoma após um período de seguimento de 20 a 30 anos, pelo que recomenda o acompanhamento a longo prazo.…”
Section: Discussionunclassified
“…No entanto, as lesões de linfoma cutâneo primário de grandes células B anaplásico geralmente são de maiores dimensões e, apesar de poderem resolver espontaneamente à semelhança da PL, não apresentam carácter recorrente. 1 A PL clássica pode associar-se a linfomas, sobretudo micose fungóide, linfoma cutâneo primário de grandes célu-las B anaplásico e doença de Hodgkin, 10 numa frequência que tem sido difícil de estabelecer, variando entre 10% a 20%, até 40% a 60% em estudos mais recentes. 10 Gruber et al estimou um risco cumulativo de 80% de desenvolver um linfoma após um período de seguimento de 20 a 30 anos, pelo que recomenda o acompanhamento a longo prazo.…”
Section: Discussionunclassified
“…However, concurrent presentation of LyP and MF has been described [13] and no histological features of MF were present in any of the regional LyP cases or in our patient. Moreover, the comprehensible idea of some authors that PALP simply reflects localized LyP has been recently questioned by Pileri et al [22], who reported a patient presenting with simultaneous patch areas as well as waxing and waning papulonodular lesions on the trunk and extremities, both manifestations characterized as LyP. Finally, further cases of PALP are on record that showed spontaneous remission as in typical LyP [18,23,24], suggesting that the patch- and plaque-like features of PALP belong to the LyP component of the lesion.…”
Section: Discussionmentioning
confidence: 99%